Perancangan UI/UX Design Aplikasi Mobile Pertanian Menggunakan Metode Design Thinking - Dimas Aditya Rama; Risqi Firdaus Setiawan (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Technology develops from time to time influenced by human activities and needs that continue to increase as well. Technological developments also play a role in helping the agricultural sector. Through technological developments, many problems in agriculture can be resolved. One of the problems is in agricultural extension activities, where farmer participation in extension activities is low in some areas. This research aims to build UI/UX design for an agricultural mobile application called Sobatani which is useful for connecting farmers with agricultural extension workers. This research uses the Design Thinking method which consists of five stages including empathize, define, ideate, prototype, and testing. The test results using the Single East Question (SEQ) method obtained a total average of 6.6, indicating that the UI design is fairly effective and successful. Although there are some misclicks, so it is necessary to iterate on the Log in and Weather Forecast pages. The use of the Design Thinking method has proven effective in understanding user needs and designing solutions that can provide these needs.